Leg Muscle Strength, Waist Flexi Hubungan Kekuatan Otot Tungkai Dan Kelentukan Pinggang Terhadap Ketepatan Shooting Futsal Di Klub Pratama Family Sungai Penuh - Ramadhan, Daffa Ikli; Alnedral, Prof; Padli, Dr.; Arifan, Ikhwanul (Jurnal Gladiator, 2023)
ABSTRACT The problem with this research is that it is suspected that the shooting accuracy of the Pratama Family Club Futsal athletes is not optimal. The purpose of this study was to determine the relationship between leg muscle strength and flexibility towards the shooting accuracy of the Primary Family Futsal Club. This type of research was a correlational study. This research was carried out in September 2022 at the Juanda Futsal field. The population in this research is 18 athletes. The sampling technique used the total sampling technique, so the number of samples in this study were 18 athletes. The instruments in this study were: 1) leg and back dynamometer, 2) sit and reach test, 3) shooting accuracy test. The data analysis technique uses simple correlation analysis and multiple correlation followed by significance test analysis. The results of this study are: 1) There is a significant relationship between leg muscle strength and the accuracy of shooting in Futsal Pratama Family athletes with the significance of the correlation results rcount 0.519 > rtable 0.468 or with significance test tcount 2.43 > ttable 1.74. 2) There is a significant relationship between flexibility and the accuracy of shooting for Futsal Pratama Family athletes with a significance correlation result of rcount 0.637 > rtable 0.468 or with a significance test tcount 3.31 > ttable 1.74, 3) There is a significant relationship between leg muscle strength and flexibility jointly on the shooting accuracy of Pratama Family Futsal athletes with a significance of the correlation results Rcount 0.672> Rtable 0.468 or with a significance test Fcount 6.17> ttable 3.68.